2006
DOI: 10.1093/aob/mcl191
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Morphometric Implications of Morphological Variation Among Flowers Within an Inflorescence: A Case-Study Using European Orchids

Abstract: This result demonstrates the strong influence of epigenesis on flower morphology and further emphasizes the importance of (a) sampling from a consistent location within the inflorescences under comparison, (b) interpreting morphometric ordinations hierarchically, building from individuals to infraspecific taxa and species via populations, and (c) considering in any microevolutionary study the potentially profound effects of the cline in flower size within each inflorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 50 publications
(73 reference statements)
2
51
0
2
Order By: Relevance
“…There is considerable potential for studies of structures repeated as a sequence along some axis, like vertebrae in the spinal column of fish or snakes [255,256], plant leaves along a shoot axis [257][258][259][260], leaflets within compound leaves [173,191,260], or flowers within an inflorescence [261]. In plants, particularly, the modular body plan provides many opportunities for exploring variation among repeated parts within individuals [262].…”
Section: Analyses Of Matching Symmetry For Complex Symmetriesmentioning
confidence: 99%
“…There is considerable potential for studies of structures repeated as a sequence along some axis, like vertebrae in the spinal column of fish or snakes [255,256], plant leaves along a shoot axis [257][258][259][260], leaflets within compound leaves [173,191,260], or flowers within an inflorescence [261]. In plants, particularly, the modular body plan provides many opportunities for exploring variation among repeated parts within individuals [262].…”
Section: Analyses Of Matching Symmetry For Complex Symmetriesmentioning
confidence: 99%
“…Table 5 lists examples of spur and labellum size ranges for different regions of Europe (Webb 1980;Komarov, Chernyakovskaya 1986;Stace 1997;Szlachetko 2001;Jeanmonod, Gamisans 2007;Lauber, Wagner 2007). Other authors mentioned only mean values of those variables; for example, Bateman and Rudall (2006) reported the mean length of spur and labellum (29 and 13.8 mm, respectively); Stpiczyńska (2003) reported a mean of 31.5 for specimens collected in the vicinity of Lublin. The specimens from the sites in NW Poland, examined in this study, showed generally smaller spur and labellum, 25.5 mm (max 34.8 mm) and 12.2 mm (max 19.8 mm), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of the spur, a component playing a key role in attracting specific pollinators, has been in the focus of great attention of botanists, both traditional and evolutionary (e.g. Nilsson 1978;Bateman, Rudall 2006;Bateman, Sexton 2008;Bateman et al 2009). …”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of European-Mediterranean Anacamptis pyramidalis show great phenotypic variability of habit, inflorescence shape, flower lip shape, lip spur length and flower color (Bateman and Rudall, 2006b;Margońska and Kowalkowska, 2008). The taxon displays three levels of ploidy: diploids (2n = 36), triploids (2n = 54) and tetraploids (2n = 72) (Bianco et al, 1991;del Prete et al, 1991;Tichy and del Prete, 2001).…”
Section: Introductionmentioning
confidence: 99%